A multi-environment nanocalorimeter with electrical contacts for use in a scanning electron microscope. Issue 6 (12th September 2017) - Yi, Feng; Stevanovic, Ana; Osborn, William A.; Kolmakov, A.; LaVan, David A.
Abstract : A multi-environment SEM nanocalorimeter showing a SnO2 nanowire under vacuum and in air along with EBIC measurements at 1 atmosphere. Abstract : We have developed a versatile nanocalorimeter sensor which allows imaging and electrical measurements of samples under different gaseous environments using a scanning electron microscope (SEM) and can simultaneously measure the sample temperature and the associated heat of reaction. This new sensor consists of four independent heating/sensing elements for nanocalorimetry and eight electrodes for electrical measurements, all mounted on a 50 nm thick, 250 μm × 250 μm suspended silicon nitride membrane. This membrane is highly electron transparent and mechanically robust enabling in situ SEM observation under realistic temperatures, environmental conditions and pressures up to one atmosphere. To demonstrate this new capability, we report here on (1) an in situ SEM-nanocalorimetry study of melting and solidification of polyethylene oxide, (2) the temperature dependence of the conductivity of a nanowire and (3) electron beam induced current (EBIC) measurements of a nanowire under vacuum and in air. Furthermore, the sensor is easily adaptable to operate in a liquid environment and is compatible with most existing SEMs. This versatile platform couples nanocalorimetry with in situ SEM imaging under various gaseous and liquid environments and is applicable to materials research, nanotechnology, energy, catalysis and biomedical applications.